The Effects of Dopants on The Physico-Chemical Properties of Vanadyl Pyrophosphate Catalysts - Tan, Kian Peng (2003)
Vanadium phosphorus oxide (VPO) is a commercial catalyst for selective oxidation of butane to maleic anhydride. The nature of the oxidant of the doped and undoped (VOhP207 catalysts derived from (i) VPO, reaction of V20s with H3P04 in isobutanol and (ii) VPD, reaction of VOP04·2H20 with isobutanol were investigated. Metal cations, namely of sodium, potassium, magnesium and bismuth, were added as dopants into (VO)2P2O7 lattice. From the Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analysis, the catalysts which have gone through a series of redox reaction do not produce the original morphology of (VO)2P207. The results indicated that the addition of dopants lowered the Brunauer-Emmet-Teller (BET) surface area of vanadyl pyrophosphate catalysts, except Bi-doped VPD catalysts. All the doped VPO and VPD catalysts have been shown a vanadyl pyrophosphate phase with three distinct peaks at 22.9°, 28.4° and 29.3° in X-ray Diffraction (XRD) analysis. The Bi-doped VPO and VPD catalysts had significantly shifted the first reduction peak to a lower temperature in H2-TPR analysis. The introduction of Bi have modified the (VOhP207 matrix and mobility of these catalyst increased. It can be seen from TPRn analysis where VPDBil increased the selectivity of butene and butadiene (selective products) and decreased the selectivity of CO and C02 (unselective products).